Nuclear-excited source of coherent and incoherent radiation with direct nuclear pumping; Applied Radiation and Isotopes; Vol. 214 - Samarkhanov K. K. Kuanysh Kanatuly; Khasenov M. Mendikhan; Batyrbekov E. G. Erlan Gadletovich; Skakov M. K. Mazhyn Kanapinovich; Gradoboev A. V. Aleksandr Vasilyevich; Bedenko S. V. Sergey Vladimirovich; Vega-Carrillo H. R. Hector Rene; Kenzhina I. E. Inesh; Askerbekov S. K. Saulet Kanybekuly; Kozlovskiy A. L. Artem Leonidovich; Zaurbekova Zh. A. Zhanna Askhatovna; Shaymerdenov A. A. Aset Abdullaevich; et al. (2024, 2024)
Title screen